Models of alliteration derivation in the Quran - Jamil H. A. Ayyash,; Salmah Ahmad,; Md. Nor Abdullah, (Universiti Kebangsaan Malaysia, 2013)
The importance of the research is drawn from the fact that it treats a rhetorical concept. Alliteration is an important science for understanding the meaning of the Quranic verses, and Alliteration Derivation presents an aspect of the rhetorical miracles of the Quran as well as reveals the stylistic beauty of the Arabic language. The research aims at highlighting the beauty of the Verses containing Derivation Alliteration and what results from them such an increase in the semantic sense of the Quran. The researchers have applied in this article the inductive approach by inducing the versus that have this type of Alliteration as well as we followed the analytical method by analyzing and interpreting the verses so giving significant expressions, creativity and innovation to the Holy Quran. We have reached by the end of the research to several important results: Alliteration is one of the most important sciences to understand the rhetorical verses of the Quran and extract ideas from it. Alliteration Derivation is also not advisable unless stated in an appropriate location, and it will be bothered if it were artificial. Moreover Alliteration Derivation gives the expressions of the Quran feature innovation, creation and innovation in finding different connotations. Additionally, it is not considered only as verbal ornaments and colorful decorations that have an eloquent impact attracting the listener, making him listen to and making it easy to hear, but also it affects the psychological aspect of the human being. As a matter of fact, the alliterated form can deceive the listener, whereas it shows you that it will repeat the meaning, and echo the pronunciation. However, it really fakes the listener by giving a new sense which is completely different from the proceeding one. At that moment, one feels extremely happy and pleased.